Periprosthetic joint infection caused by Brucella following total joint arthroplasty - Wang, Wei; Wang, Li; Dou, Haiwei; Bekarissov, Olzhas; Kaken, Habaxi (Frontiers in Surgery, 2025)
BackgroundBrucellosis is a common zoonotic infection that imposes a substantial economic burden on China, particularly in Xinjiang. This study aims to discuss the treatment of Brucella infection following total joint arthroplasty and evaluate its therapeutic effectiveness.MethodsWe conducted a retrospective case series analyzing 8 patients who developed periprosthetic joint infection (PJI) due to Brucella after arthroplasty in our department between March 2009 and March 2019. The age range of these patients was 55–79 years, with an average age of 65.6 ± 1 year. Various parameters, including the Harris hip score (HHS), knee range of motion (ROM), visual analog scale (VAS) score for pain assessment, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) level, were assessed before and after the revision surgery. Postoperative x-rays were used to assess the curative effect of revision surgery.ResultsAll patients experienced pain and elevated ESR levels. However, none of these patients exhibited deep vein thrombosis (DVT) or nerve damage. Additionally, no skin sinuses were detected. All infected patients underwent revision surgery subsequent to initial total joint arthroplasty. The follow-up period ranged from 6 to 30 months, with an average duration of 14 ± 0.5 months. After revision surgery, both HHS and Harris score assessments, as well as x-rays, were conducted to evaluate the curative effect. No cases of aseptic loosening or prosthesis fracture occurred during or after the revision operation, and no recurrence of infection were observed. The average knee ROM improved to 90 ± 3°.ConclusionsRecent clinical findings indicate that systemic antibiotic chemotherapy combined with surgical techniques is effective in treating patients following total joint arthroplasty. Revision surgery significantly improves joint function and alleviates pain.